1997
DOI: 10.1073/pnas.94.12.6132
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of a protein-repair enzyme results in the accumulation of altered proteins, retardation of growth, and fatal seizures in mice

Abstract: L-Asparaginyl and L-aspartyl residues in proteins are subject to spontaneous degradation reactions that generate isomerized and racemized aspartyl derivatives. Proteins containing L-isoaspartyl and D-aspartyl residues can have altered structures and diminished biological activity. These residues are recognized by a highly conserved cytosolic enzyme, the protein L-isoaspartate(D-aspartate) O-methyltransferase (EC 2.1.1.77). The enzymatic methyl esterification of these abnormal residues in vitro can lead to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
316
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(335 citation statements)
references
References 46 publications
15
316
3
Order By: Relevance
“…These mice exhibited slow growth and a fatal seizure disorder leading to death after an average of 42 days of age (Kim et al 1997(Kim et al , 1999Yamamoto et al 1998). In addition, PIMT-/-mice showed aberrant synaptic transmission in the CA3 region of the hippocampus, associated with an abnormal distribution of synaptic vesicles in the mossy fiber terminals (Ikegaya et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These mice exhibited slow growth and a fatal seizure disorder leading to death after an average of 42 days of age (Kim et al 1997(Kim et al , 1999Yamamoto et al 1998). In addition, PIMT-/-mice showed aberrant synaptic transmission in the CA3 region of the hippocampus, associated with an abnormal distribution of synaptic vesicles in the mossy fiber terminals (Ikegaya et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that PIMT activity is important for the maintenance of the central nervous system since PIMT-deficient mice died from progressive epileptic seizures and showed aberrant synaptic transmission in the hippocampus (Kim et al 1997(Kim et al , 1999Yamamoto et al 1998;Ikegaya et al 2001). This suggests that changes in PIMT activity in the human brain during epilepsy, particularly in the hippocampus which is the major seat of temporal lobe epilepsy, may be involved in this disease.…”
Section: Down-regulation Of Pimt In the Hippocampus Of Epileptic Patimentioning
confidence: 95%
See 2 more Smart Citations
“…We show here that PIMT levels in erythrocytes of healthy individuals fell within a narrow the level of isoaspartate-bearing proteins increases dramatically in rat PC12 cells grown in the presence range, and the level of activity appeared to be governed substantially by inheritance. Thermal stability data of a methyltransferase inhibitor (17) and in mice in which the gene encoding PIMT has been selectively from a population sample of 299 donors suggested the presence of two major alleles which were subsequently disrupted (18). The PIMT-deficient mice grow more slowly than their normal counterparts and undergo shown to be associated with the presence of an Ile/Val polymorphism recently described by Tsai and Clarke fatal seizures between 26 and 60 days after birth.…”
mentioning
confidence: 97%